2009
DOI: 10.1111/j.1747-4949.2009.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Its Role in the Pathogenesis of Ischaemic Stroke

Abstract: Stroke is one of the leading causes of mortality and morbidity, with astronomical financial repercussions on health systems worldwide. Ischaemic stroke accounts for approximately 80-85% of all cases and is characterised by the disruption of cerebral blood flow and lack of oxygen to the affected area. Oxidative stress culminates due to an imbalance between pro-oxidants and antioxidants and consequent excessive production of reactive oxygen species. Reactive oxygen species are biphasic, playing a role in normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
539
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 826 publications
(554 citation statements)
references
References 87 publications
4
539
0
11
Order By: Relevance
“…Reduced cystathionine‐transsulfuration may impair glutathione production and thereby lead to oxidative stress 7. Oxidative stress can, in turn, further impair endothelial morphology by inactivating nitric oxide,9 in addition to mediating several other biological processes such as lipid peroxidation and induction of vascular lesions 1. Notably, a previous study from a subsample of the current cohort showed that higher plasma cystathionine concentration are related to low levels of reduced glutathione,33 indicating impaired antioxidant defence 7…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Reduced cystathionine‐transsulfuration may impair glutathione production and thereby lead to oxidative stress 7. Oxidative stress can, in turn, further impair endothelial morphology by inactivating nitric oxide,9 in addition to mediating several other biological processes such as lipid peroxidation and induction of vascular lesions 1. Notably, a previous study from a subsample of the current cohort showed that higher plasma cystathionine concentration are related to low levels of reduced glutathione,33 indicating impaired antioxidant defence 7…”
Section: Discussionmentioning
confidence: 88%
“…Stroke is a leading cause of mortality and long‐term disability in the world and remains a massive public health burden 1. This highlights a pressing need to identify novel risk associations for stroke and improve our current understanding of its underlying pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress, an imbalance between the production of the reactive oxygen species and the human body's antioxidant defense mechanism,4 has been proposed as an important underlying biological mechanism mediating this association 3, 5, 6, 7. Increased oxidative stress may induce endothelial dysfunction, which is characterized by increased endothelial permeability, altered vascular tone, platelet adhesion and aggregation, and enhanced thrombogenicity 8, 9…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by high morbidity, high mortality, and a high recurrence rate therefore posing a significant burden on health resources. Ischemic stroke is the most common type of stroke that accounts for almost 80–85% of all stroke cases and is brought about by cutting off cerebral blood flow and thereby oxygen to the brain (Allen & Bayraktutan, 2009). Although a variety of risk factors have been established for ischemic stroke, about 25% of stroke cases are considered cryptogenic (Fonseca & Ferro, 2015).…”
Section: Introductionmentioning
confidence: 99%